If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + -4 = 3b + 2 Reorder the terms: -4 + 4b = 3b + 2 Reorder the terms: -4 + 4b = 2 + 3b Solving -4 + 4b = 2 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. -4 + 4b + -3b = 2 + 3b + -3b Combine like terms: 4b + -3b = 1b -4 + 1b = 2 + 3b + -3b Combine like terms: 3b + -3b = 0 -4 + 1b = 2 + 0 -4 + 1b = 2 Add '4' to each side of the equation. -4 + 4 + 1b = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 1b = 2 + 4 1b = 2 + 4 Combine like terms: 2 + 4 = 6 1b = 6 Divide each side by '1'. b = 6 Simplifying b = 6
| 5x-3y=45 | | 180+3a=2a-25 | | 4a+6=26 | | 34=-5-9t | | 40y+4-60y+12=200 | | 19x+11-3x=25-18x | | 16y=48 | | -(9x-15)+6(x-10)=-9 | | x(x+1)=7 | | 23-(-10)+(-19)= | | 10d-22+6d=12d+12 | | 23x=85 | | 3(x)=5(y)-11 | | -3(6n+4)=24 | | y/2+3=2(y-2) | | 7k-2k=25 | | 3C+9=-24 | | x^2=2x+13 | | -3(x+5)+2(x+8)=35 | | t/8-6=-12 | | 2[7-7(1-n)]+4n=-16+3[6(n+1)-3n] | | 5b^2-35b+60=0 | | 12(11p+11)+11p=275 | | 4=3(-1)-1 | | 16+7-4x=3 | | 4x+3=7x | | 5x=y-4 | | 4+a=9 | | 0.40(y+10)-0.60(y+2)=2 | | 15(14-14x)+3(9+7x)=48 | | 36=2(w*3)+2w | | -7(-5b+4)=-28 |